Performance of Grid-Connected Rooftop Solar PV System for Households during Covid-19 Pandemic - Partaonan Harahap; Faisal Irsan Pasaribu; Chandra Amirsyah Putra Siregar; Benny Oktrialdi (Journal of Electrical Technology UMY, 2021)
As we know, the need for electrical energy is increasing along with population growth and technological developments. This increase was also triggered by the growth rate of the energy demand of 6.86% per year. Most of the energy needs come from non-renewable energy, which has limitations and is not environmentally friendly. Despite being affected by Covid, this period is a momentum to start the direction of clean energy policies. The utilization of solar power can be started by utilizing a rooftop solar power system on the roof of a hotel or on the roof of other industrial buildings. As one of the research and development institutions in the housing and settlement infrastructure sector, it tries to provide alternative technology solutions through an innovative technology called PV-roof. The results of the research show that the designed roof off-grid has an average voltage and current on the first day of 13 Volts and a current of 1.8 A, and on the second day, 12.4 Volts and a current of 1.6 A, while on the third day, 12.8 Volts and current of 1.8 A. If the use of 1 battery bears a load of 450 Watts for 2.7 hours, then for users less than 5 hours, the solar charger controller capacity is 12.12 A.